BOOKS RECENTLY PUBLISHED. (Notes, 2009)
The article presents a list of books on music published recently as of December 2009, including "Sufi Rapper: The Spiritual Journey of Abd al Malik," by Abd al Malik, "Integrating Music Into the Elementary Classroom," by William M. Anderson and Joy E. Lawrence, and "The Complete Lyrics of Oscar Hammerstein II," by P. Arundhati.